Efektivitas Media Leaflet dan Film dalam Peningkatan Pengetahuan Pubertas di SMP N 226 Pondok Labu - Yanti Harjiono Hadiwiardjo; Mila Citrawati Asiyanto; Citra Ayu Aprilia (Universitas Ahmad Dahlan, 2020)
Background: Adolescent is a trantition phase from childhood to adulthood. Knowledge about puberty is important during this phase. If there is no sufficient information about it, it could cause several problems such as adolescence growth and development failure and healt problems. Health promotion to increase awareness of puberty is definitely needed by junior high students aged around 8 to 14 years old. Puberty health promotion could be delivered through visual media such as leaflet or audiovisual media such as animation film. The aim of this study was to discover effectivity of leaflet and animation film in increasing puberty awareness in students of Public Junior High School 226, Pondok Labu, South Jakarta. Method: This study was a quasi experiment with one group pre test-posttest design. Population of this study was whole students of 7th grade Public Junior High School 226. Sampling technique used was total sampling as many as 256 students. Data was analyzed by Wilcoxon test to find out effectivity of leaflet and animation film, meanwhile Mann Whitney test was used to discover effectivity between leaflet and animation film. Results: Both leaflet and animation film were effective to improving knowledge for adolescent (p-value<0,001). Conclusion: Either leaflet or animation film increased puberty awareness of students. There was no effectivity difference between both media in increasing puberty awareness of students at Public Junior High School 226.